Surdez e escola: balanço tendencial da produção especializada sobre o ensino de matemática (1974 a 2020) - Silva, Corina de Albuquerque e (2021)
The Objective of this research was to analyse the trends in academic productions about mathematics teaching for the deaf in national and international specialized journals, focusing on their authorship, in the specialized journals, in which they were published, in the mathematical content (s) and their themes. For these purposes, the collection chosen for the collect of articles was the Portal of Periodicals of the Coordination for the Improvement of Higher Education Personnel (Capes), for its wide recognition and use by the academic community and access to national and international productions, comprising productions published in the period between 1974 and 2020. An analysis was carried out based on the theoretical contributions of Bourdieu (1983) regarding the materiality of the academic productions and the scientific field. The results indicate, in national scenario, the priorization of the impact around the language, with emphasis on general themes of mathematics, while the international articles, although they also present this same priorization, presenting a higher incidence than the previous ones, regarding focuses on specific mathematical content. It is concluded that studies on the teaching of mathematics for the deaf and mandatory expressions of the disputes present in the field of education for the deaf, whose basic characteristic is the privileging of questions focusing on language over curriculum contents